Chemical Recycling of Plastic Waste: Comparative Evaluation of Environmental and Economic Performances of Gasification- and Incineration-based Treatment for Lightweight Packaging Waste - Raoul Voss; Roh Pin Lee; Magnus Fröhling (Circular Economy and Sustainability, 2022)
Chemical recycling (CR) – in enabling the use of plastic waste back as secondary carbon feedstock for production – could play a complementary role to mechanical recycling in supporting the transformation from a linear to a circular carbon economy. To date, research has predominantly focused on assessing technological aspects associated with CR of pure plastic waste streams. Little is known about its potential for treating low-quality and mixed plastic waste fractions which are unsuitable for conventional recycling and are currently incinerated. To address this gap, this investigation utilizes an integrated approach comprising of life cycle assessment and techno-economic analysis to evaluate the environmental and economic performance of CR of lightweight packaging waste via waste gasification compared to direct and indirect incineration in Germany. Results show that CR can contribute significantly – irrespective of the energy mix – to reducing climate change, terrestrial acidification, and fossil resource scarcity. In terms of economic performance, findings suggest that while CR requires higher capital investment, a multi-pronged approach which encompasses upscaling, waiver of carbon dioxide certificate costs, and price premium for CR products could increase profitability of CR to incineration. This study provides empirical support for the potential contribution of CR to complement existing strategies to combat the plastic waste challenge, and insights into market conditions which could promote its economic attractiveness. Additionally, it provides comprehensive inventory data for conventional and alternative waste treatment plants for lightweight packaging waste to inform future research on systemic assessment of CR technologies and their contributions to a circular economy.
Keywords: 330; Circular carbon economy; Life cycle assessment (LCA); Techno-economic analysis (TEA); Waste incineration; Plastic waste